Phenomenological Study: Employee Perceptions Related to Work Rotation at Bank BTN KC Bekasi - Putri, Dea Ananda (Westscience Press, 2025)
The purpose of this study is to find out how employees of Bank Tabungan Negara (BTN) KC Bekasi view work rotation and how their views and experiences are influenced by their competencies. This study conducted in-depth interviews with employees to find out the dynamics of work rotation and its impact on organizational performance as well as career growth. A qualitative approach is used to collect data. The results of the study show that most employees support work rotation. Customers' production and service increased as a result of their improved skills in performing banking actions. Some participants said that although they initially felt uncomfortable with the change in work environment, eventually they were able to adapt and feel more comfortable in a new place. In addition, this study emphasizes how important it is to create a work rotation policy that suits the needs of Employees to improve the overall performance of the company. The results of this study are expected to make a significant contribution to the advancement of human resource management theory and practice, especially in terms of work rotation in the Indonesian banking industry, where much research on this subject has not been carried out. Thus, this research not only builds on previous research, but also provides practical knowledge on how management can create policies that better suit employee needs.